Gefühlte (Un)Gerechtigkeit - Glatzer, Wolfgang (Silesian Statistical Review, 2011)
The paper is devoted to the problem of injustice felt and the social tensions connected with it. First, the classical concepts of the justice done by F.A. von Hayek, J. Rawls, M. Walzer, A. Sen and other modern concepts and searching methods are reminded. The social (in)justice is studied in two aspects: individual and connected with the problem of the distribution of goods. The paper contains the results of the investigation regarded German “old lands” and former GDR. Besides the studies of the individual injustice felt, the social, collective injustice is investigated. The social effects of the injustice felt are treated. These effects depend on the history of lands
Śląski Przegląd Statystyczny = Silesian Statistical Review, 2011, Nr 9 (15), s. 7-20
Keywords: injustice felt; distribution of good; social injustice; niesprawiedliwość odczuwana; dystrybucja dóbr; niesprawiedliwość społeczna